USAID Imarisha Jamii Program Brief - Soo, Leonard (My University, 2021)
USAID Imarisha Jamii is a 5-year program funded by the President’s Emergency Plan for AIDS Relief (PEPFAR) and the US Agency for International Development (USAID) to increase the use of quality county-led health and social services in Turkana County.
BUDGET: US$ 29,987,738 Project Period: March 2021 – September 2025 Region: Turkana County Implementing Partner: Amref Health Africa in Kenya Target group: Health workers, community health volunteers & women of reproductive age
Keywords: Imarisha Jamii Program; PEPFAR